Canal disinfection using photo-chemically activated micro-bubble emulsion, Emblica officinalis, and Nd: YAP laser on smear layer and push-out bond strength of resin-based root canal sealer to the radicular dentin - Mazen F. Alkahtany; Khalid H. Almadi (Photodiagnosis and Photodynamic Therapy, 2024)
Aims: Evaluation of the effects of the latest root canal disinfectants i.e., Micro-bubble emulsion (MBE), Neodymium-doped yttrium aluminum perovskite (Nd: YAP), Emblica officinalis (E. officinalis) on the removal of smear layer (SL) and push out bond strength (PBS) of resin-based root canal sealer to the radicular dentin. Methods: The coronal portion of sixty single-rooted human mandibular premolar teeth was precisely sectioned at the cementoenamel junction. The canals were prepared to utilize ProTaper universal rotary files till F3. All the study specimens were divided into four groups based on the disinfection regime (n = 15) Group 1: 5.25% NaOCl, Group 2: MBE, Group 3: Nd: YAP laser and Group 4: E. officinalis extract. All the canals were then finally irrigated using 17% EDTA solution as a final disinfecting agent. SL removal assessment was performed on five samples from each group using a scanning electron microscope (SEM). Ten samples from each group were then filled with root canal filling material and the roots were sectioned. Push-out test and failure mode analysis were performed using the universal testing machine (UTM) and stereomicroscope respectively. The mean scores of PBS and SL removal were compared using a one-way analysis of variance (ANOVA) and Post Hoc Tukey's HSD test p = 0.05. Results: Group-2 (MBE + EDTA) coronal section (1.50 ± 0.23) exhibited the most effective eradication of SL from the canal space. The apical third of Group-1 (NaOCl+EDTA) (2.68 ± 0.82) samples demonstrated the least effective removal of SL from the radicular canal. The maximum score of PBS of AH plus sealer to the canal dentin was exhibited by the coronal section of Group-2 (MBE + EDTA) (9.55 ± 0.45 MPa) samples. However, the apical third of Group-1 (NaOCl+ EDTA) specimens (5.16 ± 0.32 MPa) demonstrated the minimum EBS. Conclusion: MBE+ EDTA displayed better smear layer removal and bond integrity of AH plus sealer to the root canal dentin. Nd: YAP+ EDTA laser and E.officinalis displayed comparable outcomes to that of control NaOCl+ EDTA